Possibilities of ensuring the aesthetic expressiveness of Ukraine’s bridges reconstructed after war - Ostapchuk, Vitalii (Theory and practice of design, 2022)
The article describes the features of aesthetic improvement of reconstructed bridge that were destroyed during the war. As a result of the warfare operations during the russian military invasion of Ukraine, more than 300 bridges were destroyed. Now, when we have managed to push the aggressor away from north part of our country, one of the main task for us is a repair of roads and bridges. Taking into account the low financial possibilities of fighting or postwar country and the real production capacity of the factories for the manufacture of building structures, we should be ready that the reconstructed or the new bridges will be built with the standard projects of girder structures which are all look the same. So the reality makes us to admit that after a large-scale and rapid reconstruction of the lost transport structures, Ukraine will face the problem of monotonous and faceless bridges again. This means that people will perceive them as structures only for transport pass but not as a landmarks. Therefore there is a possible way to avoid this — aesthetic improvement during the further exploitation of these bridges (when there is money for that) which doesn’t include a structure changing. Here are some ways to achieve that: 1. Creation of “Design-code” of bridges which includes certain color, texture, relief of surfaces non-bearing elements of a bridge, unique fences, lighting atc. 2. Imitation of cable-stayed or suspension structure using the “pseudo structures” built on the separate foundation so that they won’t create any extra load on existing bridge. 3. Extension of the existing bridge with a pedestrian one (on the separate foundation again) which is a good decision for bridges in settlements or the overpasses above the big road with high traffic. 4. Construction of a pedestrian bridge nearby the existing one. This is the way to improve bridge environment in the city and add some interesting place on the quay. This is clear that the perfect decision is to design the great bridge without any further improvements. It’s much better than imitation of different structures. But these improvements may become the first step to change people’s attitude towards bridges as landmarks rather than purely utilitarian structures. All of this will increase the demand for aesthetic component of bridges and overpasses and it will encourage designers and customers to create bridges that could became a landmark of a region.